2019
DOI: 10.1186/s12939-019-1096-x
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of health stock and the relation to national wealth

Abstract: BackgroundThe decline in global and between-country health inequality is a major challenge to overcome. However, few studies have systematically investigated the relationship between inequality of health stock and national wealth. From an economic perspective, health can be viewed as a durable capital stock that produces an output of healthy time. Therefore, in this paper, we focused on health capital to investigate the relationship between inequalities of national health and national wealth.MethodsBased on he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For example, as the real GDP per capita of the world increased by 180% between 1970 and 2007 and infant mortality fell by 50% ( 25 ). The study of Jumbri et al ( 26 ) also showed a link between economic status and health development. They found that residents of areas with better economic conditions are more likely to pursue high-quality health, which is yet another piece of evidence of the relationship between economics and health.…”
Section: Discussionmentioning
confidence: 92%
“…For example, as the real GDP per capita of the world increased by 180% between 1970 and 2007 and infant mortality fell by 50% ( 25 ). The study of Jumbri et al ( 26 ) also showed a link between economic status and health development. They found that residents of areas with better economic conditions are more likely to pursue high-quality health, which is yet another piece of evidence of the relationship between economics and health.…”
Section: Discussionmentioning
confidence: 92%
“…Compared with the existing energy efficiency indicators, one of the main advantages of EIWB is that EIWB provides a new perspective of thinking and research. EI and TFEE both define energy efficiency as the relationship between energy input and economic output [15][16][17], while economic output cannot be simply equal to the health status and well-being of residents [18]. In other words, at the beginning of design, EI and TFEE did not highlight that the ultimate goal of economic development is to achieve development of human being.…”
Section: Introductionmentioning
confidence: 99%